2022
DOI: 10.7759/cureus.27694
|View full text |Cite
|
Sign up to set email alerts
|

Heart Failure With Reduced Ejection Fraction Caused by Osimertinib in a Patient With Lung Cancer: A Case Report and Literature Review

Abstract: Osimertinib is widely used for the treatment of advanced lung cancers harboring epidermal growth factor receptor (EGFR) mutations. Because of its inhibitory activity on the human epidermal growth factor receptor 2 pathway, osimertinib-induced cardiotoxicity is concerning. Large-scale international clinical studies revealed a subclinical decline in the left ventricular ejection fraction (LVEF) with osimertinib, which allowed a continuation of the drug. Only a few studies have reported symptomatic heart failure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Additionally, the previously reported cases of heart failure post-osimertinib administration typically manifested within a few weeks to several months, with 7 months being the longest documented duration [7,8]. However, the emergence of heart failure symptoms in this case, a notable 18 months following the initiation of osimertinib, significantly extends this observed timeline and challenges existing perceptions regarding the onset of cardiotoxicity.…”
Section: Discussionmentioning
confidence: 50%
“…Additionally, the previously reported cases of heart failure post-osimertinib administration typically manifested within a few weeks to several months, with 7 months being the longest documented duration [7,8]. However, the emergence of heart failure symptoms in this case, a notable 18 months following the initiation of osimertinib, significantly extends this observed timeline and challenges existing perceptions regarding the onset of cardiotoxicity.…”
Section: Discussionmentioning
confidence: 50%
“…Additionally, some genetic elements play an important role in NSCLC development, including EGFR mutations, which may even explain the occurrence of NSCLC in never-smoker patients as they harbor EGFR mutations more frequently. [5] Heart failure (HF) is a clinical syndrome that develops when the heart's function is impaired and working less efficiently than normal thus it cannot keep up with the metabolic needs of the body [22]. HF has been considered a major public health issue in recent years due to its growing prevalence [23].…”
Section: Discussionmentioning
confidence: 99%
“…Anticancer treatment cardiotoxicity is typically classified into two categories; type I cardiotoxicity which is caused by anthracyclines is irreversible and is additive in a dosedependent manner. On the other hand, type II cardiotoxicity is reversible and is caused by suppression of the HER2 signaling pathway [5].…”
Section: Introductionmentioning
confidence: 99%
“…A post hoc analysis of the FLAURA and AURA3 trials observed a decrease in LVEF of ≥10 percentage points to an absolute value of <50% in 3.9% of patients [41]. The data did not demonstrate a significant causal relationship, though several recent case reports have observed reversible osimertinib-induced cardiomyopathy [14,15,42]. The most frequent grade 3-4 toxicities included: neutropenia (3.4%), lymphopenia (3.3%), and hyponatremia (3.4%).…”
Section: Third Generation Osimertinibmentioning
confidence: 94%